DIGITAL ECONOMY IN SEE-6 COUNTRIES: Analysis - Janevski, Zoran; Petkovski, Vladimir (SEEA, 2017)
Digitization, which has been taking place for several decades, has affected almost every sector of the economy. The digital transformation started with the first computer revolution in the 60s, enabling task automation and process standardization. This is followed by the second information and communication technology (ICT) revolution, which was all about companies using the Internet as a standard channel of communication and a way of doing business. However, during the last two decades, the radical changes that were brought about by ICT, known as the third ICT revolution, have enhanced the full potential of digital revolution introducing the phenomenon of Digital Economy. It means basically 'Digitization of Everything’ and it is based on the latest technological developments such as Cloud Computing, Mobile Computing, Big Data and Internet of Things.
Keywords: Digital Economy; Digitization; digital transformation